Royal chancery after 1066 - Timofeeva, Olga (Neuphilologische Mitteilungen, 2022)
This paper explores linguistic and sociolinguistic mechanisms that facilitated collaboration between English and Norman administrators in the decades following the Norman Conquest. First, a community of royal and episcopal chancellors and scribes is reconstructed from historical and documentary sources and their ties and networks are described. In the second step, two subcorpora are used to illustrate the processes of lexical selection and focusing in their common professional language, Latin: royal writs of William I and circuit returns of the Domesday inquest for the South-West. Both parts of the study demonstrate high involvement of Norman actors in the leading bureaucratic positions but, at the same time, point to their wide collaboration with the local administrative and scribal personnel. As a result, the two vernaculars are mutually enriched with new professional vocabulary, while in the written Latin standard, common to both, compromise lexical features emerge.